Mapping multiple climate-related hazards in South Asia - Amarnath, Giriraj; Alahacoon, Niranga; Smakhtin, Vladimir U.; Aggarwal, Pramod K. (International Water Management Institute, 2017)
This Research Report presents the first comprehensive overview of the multiple climate hazard risks, and the proposed key issues and challenges facing the South Asian region. This report suggests methods for mapping such risks and estimating their impacts on people and agriculture in South Asia. Regional, country-wise and sub-national assessment of five climate-related risks – floods, droughts, extreme rainfall, extreme temperature and sea-level rise – is carried out. The approach involves overlaying climate hazard, sensitivity and adaptive capacity maps, and follows the vulnerability assessment framework of the Intergovernmental Panel on Climate Change (IPCC). A combined index based on hazard, exposure and adaptive capacity is introduced to identify areas susceptible to extreme risk. There is a lack of a systematic and comprehensive risk assessment capturing multiple climate hazards for the entire South Asian region and the need for a common framework for risk assessment. While this approach is well grounded in theories and integration of various spatial data including remote sensing data to derive hazard information, there is a clear need for linking additional elements from the ground at a finer scale among various sectors in developing comprehensive risk assessment information for a disaster risk management plan and promoting risk financing strategies.